Efektivitas Pendekatan Mindfulness Terhadap Siswa yang Mengalami Stres Akademik - Fastina, Lina (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025)DO - 10.24843/PJIIB.2025.v25.i01.p20, 2025)
Academic Stress is a challange experienced by students, affecting their psychological well-being and academic performance. One affactive approach to managing academic stress is through mindfulness. The purpose of this research is to investigate the impct of mindfulness on academic stress at SMK WH Surabaya. This reseacrh employs a descriptive quantitative method, utilizing instrument-based data collection techniques, with a sample compirising grade 10 students from SMK WH Surabaya experiencing academic stress. This Research’s sampling involved 10 respondents form the same cohort. This research reveals that 50% of respondents experienced high-level acaedemic stress, 20% moderate, and 30% low-level academic stress.